You are what you eat: Microplastics in the feces of young men living in Beijing - Zhang, Na; Li, Yi Bin; He, Hai Rong; Zhang, Jian Fen; Ma, Guan Sheng (The Science of the total environment, 2021)
Microplastics have been widely detected in the environment and marine organisms. However, few studies have investigated the presence of microplastics in humans. This preliminary study identified and quantified the microplastic content in human feces. A total of 26 young male students aged 18–25 years were recruited from Beijing, China. A self-administered 7-day 24-h fluid intake record was used to document fluid intake, and food intake was recorded for 3 days. Feces were collected by participants using a sterile fecal collector. Microplastics in the remaining fecal residues were measured and identified using fourier transform infrared micro-spectroscopy. Eventually, twenty-four participants completed the study. The fecal samples of 23 (95.8%) participants tested positive for microplastics. In these 23 samples, the abundance of microplastics varied from 1 particle/g to 36 particles/g (size 20 to 800 μm). The summed mass of all microplastic particles per participant ranged from 0.01 to 14.6 mg. Qualitative analysis of the microplastics indicated the presence of one to eight types of microplastics in each sample, with polypropylene (PP) being the most abundant; it was found in 95.8% of fecal samples. We examined associations between water intake habits and the abundance of microplastics in their feces. A moderate correlation was observed between packaged water and beverage intake and microplastic abundance in feces (r = 0.445, P = 0.029). Various types of microplastics were detected in human feces, with PP being found in the highest proportion. There may be an association between water intake habits and microplastic abundance in feces. [Display omitted] •Microplastics have been found in human feces.•The highest proportion of microplastic components was polypropylene.•Sources of water intake may one of the influencing factors on the content of microplastics in the human gastrointestinal tract.•More attention should be paid to the widespread existence of microplastics and its health effects.